Otsu thresholding method based on projection of cross section for image segmentation - Chao-dong FAN; Hong-lin OUYANG; Le-yi XIAO (Tongxin xuebao)
Due to the disadvantages existing in the conventional three-dimensional Otsu (3D Otsu) method, such as poor anti-noise capability, high computational complexity and difficulty to extend to multilevel thresholding, a new Otsu thresholding method based on projection of cross section was proposed. A plane perpendicular to the main diagonal is used to cross the 3D histogram. Then the projections to the main diagonal from the points in the cross section, are used to establish a new histogram. Based on the histogram, the image can be segmented by 1D Otsu. In order to further enhance the anti-noise capability, the post-processing strategy based on threshold is applied to the processed image. The experi-mental result shows that this method has significant improvements in computational efficiency and anti-noise capability, and can segment the images corrupted with different noises well.